2019
DOI: 10.1080/15384101.2019.1638192
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory signaling in genomically instable cancers

Abstract: Recent studies have shown that genomic instability in tumor cells leads to activation of inflammatory signaling through the cGAS/STING pathway. In this review, we describe multiple ways by which genomic instability leads to cGAS/STING-mediated inflammatory signaling, as well as the consequences for tumor development and the tumor microenvironment. Also, we elaborate on how tumor cells have apparently evolved to escape the immune surveillance mechanisms that are triggered by cGAS/STING signaling. Finally, we de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 188 publications
(237 reference statements)
1
20
0
Order By: Relevance
“…This indicates a possible altered response to cytosolic dsDNA in the tumor cells, as DNA can already be present in their cytosol. The presence of DNA in the cytosol of tumor cells was also demonstrated in previous studies primarily due to genomic instability [ 30 , 31 ]. This could explain the more potent response in RAW 264.7 macrophages, since these cells are the first line of defense against microorganisms and do not have a high baseline level of DNA in their cytosol, although they were derived from a tumor.…”
Section: Discussionmentioning
confidence: 99%
“…This indicates a possible altered response to cytosolic dsDNA in the tumor cells, as DNA can already be present in their cytosol. The presence of DNA in the cytosol of tumor cells was also demonstrated in previous studies primarily due to genomic instability [ 30 , 31 ]. This could explain the more potent response in RAW 264.7 macrophages, since these cells are the first line of defense against microorganisms and do not have a high baseline level of DNA in their cytosol, although they were derived from a tumor.…”
Section: Discussionmentioning
confidence: 99%
“…Mild DNA damage normally induces cell cycle arrest, while severe injury can activate the senescence program or the death programs; the latter includes apoptosis, mitotic catastrophe, autophagy, and necrosis [21].p53 plays a pivotal role in determining the fate of the cells, and, in the context of senescence, its activation can take place in a DDR-dependent or DDR-independent way [22,23]. In the first case, telomere erosion, DNA damage, as well as hyperactivation of oncogenes and inactivation of onco-suppressors (oncogene induced senescence, OIS) resulting from replicative stress activate the DNA damage repair cascade [24]. DDR activates the stress sensors' telangiectasia-muted (ATM) or ataxia telangiectasia and Rad3-related (ATR) kinases.…”
mentioning
confidence: 99%
“…Previous reports have shown that the innate immune STING-TBK1-IRF3 pathway plays an important role in anti-cancer immunity in vivo via activation of the type I interferon (IFN) response. ( 20, 30, 32 ) Functionally, cancer cell production of type I IFN enhances recruitment of natural killer (NK) cells, T lymphocytes, and macrophages. ( 20, 30, 32 ) Cytotoxic T lymphocytes, NK cells and macrophages play major roles in controlling tumor growth and thus we decided to assess if mtp53 modulated the immune infiltration within the tumor microenvironment.…”
Section: Resultsmentioning
confidence: 99%
“…( 20, 30, 32 ) Functionally, cancer cell production of type I IFN enhances recruitment of natural killer (NK) cells, T lymphocytes, and macrophages. ( 20, 30, 32 ) Cytotoxic T lymphocytes, NK cells and macrophages play major roles in controlling tumor growth and thus we decided to assess if mtp53 modulated the immune infiltration within the tumor microenvironment. Whereas PLVX tumors had an abundance of both CD4+ and CD8+ T-lymphocytes, the p53R249S tumors showed relatively less infiltration by these cells.…”
Section: Resultsmentioning
confidence: 99%